The physics of fast reactor operation and design proceedings of an international conference at the Institution of Civil Engineers, London SW1, 24-28 June 1969. (British Nuclear Energy Society, 1969)
Proceedings of an international conference organised by the British Nuclear Energy Society, held on 24-27 June 1969.